(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The interaction of tungsten (VI) with tartaric acid is studied by methods of ion exchange and spectral photometry. It is established that at the indicated interaction the complexes with M ratio 1:1 ([WO2(HC4H4O6 )]+) and 1:2 ([WO2(HC4H4O6)2]0) appears. Stepwise and general stability constants for the complexes are defined.